Exploring the role of gender and women in the political economy of health in armed conflict: a narrative review - Kristen Meagher; Bothaina Attal; Preeti Patel (BMC, 2021)
Abstract Background The ripple effects of protracted armed conflicts include: significant gender-specific barriers to accessing essential services such as health, education, water and sanitation and broader macroeconomic challenges such as increased poverty rates, higher debt burdens, and deteriorating employment prospects. These factors influence the wider social and political determinants of health for women and a gendered analysis of the political economy of health in conflict may support strengthening health systems during conflict. This will in turn lead to equality and equity across not only health, but broader sectors and systems, that contribute to sustainable peace building. Methods The methodology employed is a multidisciplinary narrative review of the published and grey literature on women and gender in the political economy of health in conflict. Results The existing literature that contributes to the emerging area on the political economy of health in conflict has overlooked gender and specifically the role of women as a critical component. Gender analysis is incorporated into existing post-conflict health systems research, but this does not extend to countries actively affected by armed conflict and humanitarian crises. The analysis also tends to ignore the socially constructed patriarchal systems, power relations and gender norms that often lead to vastly different health system needs, experiences and health outcomes. Conclusions Detailed case studies on the gendered political economy of health in countries impacted by complex protracted conflict will support efforts to improve health equity and understanding of gender relations that support health systems strengthening.